c-MYC is a radiosensitive locus in human breast cells - Wade, M. A.; Sunter, N. J.; Fordham, S. E.; Long, A.; Masic, D.; Russell, L. J.; Harrison, C. J.; Rand, V.; Elstob, C.; Bown, N.; Rowe, D.; Lowe, C.; et al. (Oncogene, 2015)
Ionising radiation is a potent human carcinogen. Epidemiological studies have shown that adolescent and young women are at increased risk of developing breast cancer following exposure to ionising radiation compared with older women, and that risk is dose-dependent. Although it is well understood which individuals are at risk of radiation-induced breast carcinogenesis, the molecular genetic mechanisms that underlie cell transformation are less clear. To identify genetic alterations potentially responsible for driving radiogenic breast transformation, we exposed the human breast epithelial cell line MCF-10A to fractionated doses of X-rays and examined the copy number and cytogenetic alterations. We identified numerous alterations of c-MYC that included high-level focal amplification associated with increased protein expression. c-MYC amplification was also observed in primary human mammary epithelial cells following exposure to radiation. We also demonstrate that the frequency and magnitude of c-MYC amplification and c-MYC protein expression is significantly higher in breast cancer with antecedent radiation exposure compared with breast cancer without a radiation aetiology. Our data also demonstrate extensive intratumor heterogeneity with respect to c-MYC copy number in radiogenic breast cancer, suggesting continuous evolution at this locus during disease development and progression. Taken together, these data identify c-MYC as a radiosensitive locus, implicating this oncogenic transcription factor in the aetiology of radiogenic breast cancer.
Keywords: Breast cancer